Detection of novel Fabry disease‐associated pathogenic variants in Japanese patients by newborn and high‐risk screening. Issue 11 (5th October 2020) - Sawada, Takaaki; Kido, Jun; Sugawara, Keishin; Matsumoto, Shirou; Takada, Fumio; Tsuboi, Kazuya; Ohtake, Akira; Endo, Fumio; Nakamura, Kimitoshi
Abstract: Background: In Japan, newborn and high‐risk screening for Fabry disease (FD), an inherited X‐linked disorder caused by GLA mutations, using dried blood spots was initiated in 2006. In newborn screening, 599, 711 newborns were screened by December 2018, and 57 newborns from 54 families with 26 FD‐associated variants were detected. In high‐risk screening, 18, 235 individuals who had symptoms and/or a family history of FD were screened by March 2019, and 236 individuals from 143 families with 101 FD‐associated variants were detected. Totally 3, 116 variants were detected; 41 of these were not registered in Fabry‐database.org or ClinVar and 33 were definitely novel. Herein, we report the clinical outcomes and discuss the pathogenicity of the 41 variants. Methods: We traced nine newborns and 46 individuals with the 33 novel variants, and nine newborns and 10 individuals with eight other variants not registered in the FD database, and analyzed the information on symptoms, treatments, and outcomes. Results: Thirty‐eight of the 46 individuals with the 33 novel variants showed symptoms and received enzyme‐replacement therapy and/or chaperone treatment. Conclusion: Delayed diagnosis should be avoided in patients with FD. Our results will help clinicians diagnose FD and determine the appropriate treatment for patients with these variants. Abstract : Nine newborns and 46 individuals with 33 novel variants, and nine newborns and 10 individuals with eight other variants not registered in the FD database were traced and the information on symptoms, treatments, and outcomes was analyzed. Thirty‐eight of 46 individuals with 33 novel variants had symptoms and received enzyme replacement therapy and/or chaperone treatment.